KERJA SAMA PENGIRIMAN PEKERJA MIGRAN INDONESIA KE JEPANG MELALUI PROGRAM VISA SPECIFIED SKILLED WORKER (SSW) - Afnur, Silvi Ramadani; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Japan is facing demographic problems, namely an ageing population and low birth rates. This situation has led to a shortage of working-age people needed to fill production activities. This study aims to determine how the deployment of Indonesian migrant workers (PMI) in the careworker sector is implemented through the Specified Skilled Worker (SSW) visa programme. The research method used is a descriptive qualitative approach with literature review data collection techniques. This study employs K.J. Holsti's theory of international cooperation. The findings indicate that initially, there was little interest in sending careworkers to Japan, but this interest has steadily increased in subsequent years. One reason for this increase is the ongoing growth of Japan's elderly population, and the SSW cooperation benefits both countries, each with their own interests. Keywords: Cooperation, Migrant Worker, Specified Skilled Worker